(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The entrepreneurship development programme was developed in the form of treatment with specific objectives, catering to the needs, requirements and interests of the inmates, which was expected to bring transformation in their thinking attitude, notions and behavioural pattern, to enable them to grow around physically, intellectually, emotionally and socially. The educational programme, conducted in adequately homely atmosphere, love, acceptance, appreciation and understanding could provide proper outlet to intellectual, emotional energy and creative expression, was expected to strengthen them from inside so that they can face challenges of life with courage and determination, so that they are normal healthy useful citizen not only of the Nation but of the World.Hence the researcher took 30 samples for the study and present the result.